International and interregional migration theory and evidence - Rivera-Batiz, Francisco L (World Scientific Publishing Company Pte Limited, 2018)
"Global and regional migration flows have exploded in the last few decades. Written by renowned migration expert, Francisco L Rivera-Batiz, this book provides a collection of articles offering a comprehensive overview of the economic analysis of migration flows and the associated policy issues. A rich discussion of the various theoretical approaches and empirical evidence available in economics is presented to analyze international and interregional labor migration. Furthermore, policy reforms, such as immigration policy changes made in the US and other countries in recent years, as well as innovative new approaches are examined. The chapters in the book focus on the economic impact of immigration, the consequences of the brain drain for developing countries, the characteristics of migrants and how they fare in host countries, the policy controversies surrounding undocumented immigrants, the determinants of attitudes and opinions about migrants, and the causes and consequences of interregional and internal migration. Overall, the book provides a guide for the serious, scientific analysis of migration flows."--
Includes bibliographical references
Keywords: Emigration and immigration / Economic aspects; Migrant labor / Economic aspects; Emigration and immigration / Government policy; Illegal aliens / Government policy; Brain drain; Electronic books; Migration